Innovation in the public sector – opportunities for peripheral regions - Steinsson, Daði Már; Ottósson, Hannes; Torfason, Magnús Þór (Research in applied business and economics, 2024)
Entrepreneurship and innovation in the private sector are often considered when examining the contribution of innovation to growth and quality of life. Such innovation is certainly important, but it is no less necessary that the part of the economy that belongs to the public sector develops in line with the new times. This article examines innovation in the public sector in Iceland, more specifically innovation at the state and ministerial level as well as workplaces at the municipal level. Our theretical approach builds on theories regional innovation. The underlying data was obtained through a detailed survey, conducted among workplaces at both the state and local (municipal) authorities. The research utilizes regression analysis and graphical representation, to compare innovation in Iceland by region to examine how it fits into theories on regional innovation. The results indicate that there is somewaht less innovation at the geographical periphery, i.e. outside of the capital area. That result is in accordance with traditional theories about regional innovation and about innovation on the geographical periphery. But it also appears that this difference is smaller when it comes to workplaces at the municipal level than in state institutions. This fits with newer theories about innovation at the periphery, which emphasize that there are many ways to define the context between the core and the periphery, including social networks and organizational issues. We also look at what motivations lie behind innovation projects and what value they are considered to have delivered, both in the capital area and outside of it. Gjarna er horft til frumkvöðlastarfsemi og nýsköpunar í einkageiranum í samhengi við þátt nýsköpunar í auknum lífsgæðum. Slík nýsköpun er vissulega mikilvæg, en ekki er síður nauðsynlegt að sá hluti hagkerfisins sem tilheyrir hinu opinbera þróist í takt við nýja tíma. Í þessari grein er til rannsóknar nýsköpun í opinbera geiranum á Íslandi, nánar tiltekið nýsköpun hjá ríkisstofnunum og hjá ...